돈적리 균의 분리, 검출을 위한 수송배지의 비교 - 조세지(Se Ji Cho); 김종완(Jong Wan Kim); 김하영(Ha Young Kim); 오상익(Sang Ik Oh); 정소정(So Jeong Jeong); 정지아(Ji A Jung); 조아라(A Ra Cho); 이명헌(Myoung Heon Lee); 조호성(Ho Seong Cho); 변재원(Jae Won Byun) (Korean journal of veterinary research, 2015)
Brachyspira (B.) hyodysenteriae is a causative agent of swine dysentery that is responsible for death andeconomic losses in the pig industry. It is imperative that clinical samples be delivered fresh for accurate diagnosis. Theviability and DNA detection of B. hyodysenteriae using lab-made (phosphate buffered saline and modified tryptic soybroth) or commercial transport media (C, D, and E) were compared by culturing and real-time PCR at 4oC or roomtemperature (RT), respectively. B. hyodysenteriae grown in D (Anaerobe Systems, USA) and E (Starplex Scientific, Canada)media was viable for 4 days at 4oC and RT. However, B. hyodysenteriae in A, B, and C (culture swab; BD Biosciences,USA) media were not recovered after 2 days at RT. Ct values for real-time PCR at 4oC and RT ranged from 27.2 ± 2.1(C) to 29.6 ± 0.5 (B), and 28.0 ± 0.9 (E) to 30.2 ± 1.5 (B), respectively. Considering the field conditions, it is importantthat transport media is used for specimen isolation and PCR to obtain an accurate diagnosis of swine dysentery. KCI Citation Count: 0